Successful complex endovascular treatment of a contained rupture of a thoracoabdominal aortic aneurysm caused by Mycobacterium bovis after intravesical Bacillus Calmette-Guerin immunotherapy for bladder cancer - Laina Passos; Vaiva Dabravolskaite, MD; Drosos Kotelis, MD; Vladimir Makaloski, MD; Michel Bosiers, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
A 71-year-old man underwent urgent endovascular repair using an inner branched endograft for a contained rupture of the visceral aorta. The patient initially improved, but later deteriorated. Positron emission tomography with computed tomography 9 months after surgery revealed perigraft inflammation. Mycobacterium bovis Bacillus Calmette-Guérin was identified from a hematoma puncture. He had undergone intravesical Bacillus Calmette-Guérin therapy 16 months earlier for bladder cancer. This led to an infected native aortic aneurysm. To our knowledge, this is the first reported case of infected native aortic aneurysm treated with an inner branched endograft. This case highlights the diagnostic challenges and suggests endovascular repair as a feasible option in selected high-risk patients.